Infected connections: Unraveling the impact of a bacterial symbiont on ant-aphid partnership - Margaux Jossart; Thierry Hance; Claire Detrain (PLoS ONE, 2025)
The multitrophic plant-aphid-ant system is a model widely studied in ecology and evolutionary biology. Within this system, bacterial symbionts can circulate and may modify the relationships between partners. A common symbiont of aphids, Serratia symbiotica, shows a wide variety of strains with different lifestyles, one of them being associated with the aphid gut and found in the digestive tract of aphid-tending ants. This free-living S. symbiotica strain induces fitness costs on its aphid host which can be offset by a lower selective pressure exerted by parasitoids. In this paper, we investigated whether this aphid gut-associated bacterium may alter the mutualistic relationships between Aphis fabae aphids and Lasius niger ants. Aphids infected with S. symbiotica showed a reduced population growth, this negative effect being attenuated in the presence of aphid-tending ants. This bacterium also reduced the ant interest in honeydew-producing aphids: they were less likely to visit plants bearing S. symbiotica-infected aphids, they ingested fewer honeydew droplets and they took a longer time before deciding to feed on released honeydew. The bacterium thus makes honeydew less palatable for ant foragers, most probably by altering its composition. This suggests that the free-living S. symbiotica strain may promote a gradual abandonment of infected aphids by ants and ultimately jeopardize the ant-aphid mutualistic relationship. We speculate about bacteria-induced consequences of reduced ant protection against aphid natural enemies and increased host plant defense as due to a potential redirection of ant foraging towards extrafloral nectaries as an alternative sugar resource.